Enzyme Inhibitory Potential of Ligustrum lucidum Aiton Berries - Paula, Vanessa B. (Molecules, 2019)
Ligustrum lucidum Aiton and its berries have been used in Chinese traditional medicine for around two thousand years. In the present study, L. lucidium berries harvested in two regions of Portugal were studied. Haemolytic activity and inhibition of oxidative haemolysis as well as the enzyme inhibitory activities (α-amylase enzyme and acetylcholinesterase) were assessed. Results suggest that the different biological activities varied according to the region where samples were collected. Results demonstrated that the sample obtained from region R1 was the most efficient extract for all parameters evaluated, presenting the lowest values of IC(50), 10.67 ± 0.46 μg/mL for the inhibition of erythrocyte oxidative haemolysis, 58.28 ± 3.77 μg/mL for the α-amylase enzyme and 67.67 ± 2.10 μg/mL for the acetylcholinesterase inhibition. L. Lucidum berries may be an interesting source of compounds for use in the development of the therapeutic armamentarium for diseases where enzymatic disruption is believed to play a role.